2006
DOI: 10.1002/pssb.200672572
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state of nanocrystalline BaTiO3 up to 52 GPa at room temperature

Abstract: We have performed in situ high pressure X-ray powder diffraction experiments on nanocrystalline BaTiO 3 (average particle size 40 nm) up to 52 GPa using synchrotron X-rays in the angle dispersive geometry with a diamond anvil cell. In order to understand the grain size effect on the tetragonal (P4mm) to cubic (Pm3m) phase transition and the compressibility, experiments were also carried out on bulkBaTiO 3 up to 36 GPa. The results show nanoBaTiO 3 is less compressible than the bulkBaTiO 3 and the phase transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We believe that both differences arise from the fact that the samples are very different, one being a crystal while the other is a powder. Similar effects have been observed in BaTiO 3 [54]. The phase transition pressures of crystalline and powder BaTiO 3 are 2.2 GPa and 4.1 GPa, respectively.…”
Section: Figuresupporting
confidence: 79%
“…We believe that both differences arise from the fact that the samples are very different, one being a crystal while the other is a powder. Similar effects have been observed in BaTiO 3 [54]. The phase transition pressures of crystalline and powder BaTiO 3 are 2.2 GPa and 4.1 GPa, respectively.…”
Section: Figuresupporting
confidence: 79%
“…Although studies of the phase stability of nanostructures under high pressure have attracted considerable interest in recent years, they were focused mainly on nonferroelectric materials exhibiting first-order pressure-induced phase transformations to denser structures. Pressure dependence studies of nanocrystalline ferroelectrics and antiferroelectrics are scarce and to the best of the authors' knowledge such studies have been reported only for BaTiO 3 [9][10][11][12] and NaNbO 3 [13]. These reports showed that studies of ferroelectric and antiferroelectric nanostructures under pressure are of great interest since such materials are particularly sensitive to surface effects.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent dielectric studies of BaTiO 3 perovskite showed that at room temperature the transition from the tetragonal ferroelectric phase to the cubic paraelectric should be observed at about 2.6 GPa and 2.5 GPa for bulk and 60 nm crystallites, respectively [9,10]. However, when the crystallite size decreases to 40 nm, the critical pressure P c increases to 4.1 GPa [11]. Moreover, the cubic phase is stable up to 52 GPa for the 40 nm crystallites and at least to 36 GPa for bulk BaTiO 3 [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed close agreement between the values of the bulk modulus independently computed with ELASTCON and EOS methods. There have been attempts [29][30][31] to compute the different properties of tetragonal BaTiO 3 . However, the computational values of elastic constants and bulk modulus of tetragonal BaTiO 3 are not available in the literature.…”
Section: Discussionmentioning
confidence: 99%